Relationship between perceived exertion during exercise and subsequent recovery measurements - Mann, T. N.; Lamberts, R. P.; Nummela, A.; Lambert, M. I. (Biology of Sport, 2017)
The return towards resting homeostasis in the post-exercise period has the potential to represent the internal training load of the preceding exercise bout. However, the relative potential of metabolic and autonomic recovery measurements in this role has not previously been established. Therefore the aim of this study was to investigate which of 4 recovery measurements was most closely associated with Borg's Rating of Perceived Exertion (RPE), a measurement widely acknowledged as an integrated measurement of the homeostatic stress of an exercise bout. A heterogeneous group of trained and untrained participants (n = 36) completed a bout of exercise on the treadmill (3 km at 70% of maximal oxygen uptake) followed by 1 hour of controlled recovery. Expired respiratory gases and heart rate (HR) were measured throughout the exercise and recovery phases of the trial with recovery measurements used to calculate the magnitude of excess post-exercise oxygen consumption (EPOCMAG), the time constant of the EPOC curve (EPOCt), 1 min heart rate recovery (HRR60s) and the time constant of the HR recovery curve (HRRt) for each participant. RPE taken in the last minute of exercise was significantly associated with HRR60s (r=-0.69), EPOCt (r=0.52) and HRRt (r=0.43) but not with EPOCMAG. This finding suggests that, of the 4 recovery measurements under investigation, HRR60s shows modest potential to represent inter-individual variation in the homeostatic stress of a standardized exercise bout, in a group with a range of fitness levels.